2022
DOI: 10.2147/copd.s333251
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Key Immune-Related Genes in Chronic Obstructive Pulmonary Disease Based on Immune Infiltration Analysis

Abstract: Purpose: Chronic obstructive pulmonary disease (COPD) is a major cause of death and morbidity worldwide. A better understanding of new biomarkers for COPD patients and their complex mechanisms in the progression of COPD are needed. Methods: An algorithm was conducted to reveal the proportions of 22 subsets of immune cells in COPD samples. Differentially expressed immune-related genes (DE-IRGs) were obtained based on the differentially expressed genes (DEGs) of the GSE57148 dataset, and 1509 immunerelated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As a scaffolding protein in many protein-protein interactions, ANHAK can coordinate a variety of biological processes, including tumor suppression and immune regulation [ 43 ]. ANHAK is the pro-viral factor for SARS-CoV-2 infection [ 44 ], while it is associated with COVID-19 in the progression of chronic obstructive pulmonary disease (COPD) [ 45 ]. Notably, we identified two genes ( TRAF3IP3 and LFNG ) that have not been reported to be associated with COVID-19, which may be potential COVID-19 biomarkers or involved in the immune response to COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…As a scaffolding protein in many protein-protein interactions, ANHAK can coordinate a variety of biological processes, including tumor suppression and immune regulation [ 43 ]. ANHAK is the pro-viral factor for SARS-CoV-2 infection [ 44 ], while it is associated with COVID-19 in the progression of chronic obstructive pulmonary disease (COPD) [ 45 ]. Notably, we identified two genes ( TRAF3IP3 and LFNG ) that have not been reported to be associated with COVID-19, which may be potential COVID-19 biomarkers or involved in the immune response to COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Within the TME, DCs can be functionally impaired, leading to reduced anti-tumour immune responses. It has been recently demonstrated that the lung tissues of patients with COPD have a peculiar immune cell distribution, containing a high number of resting NK cells, activated DCs, and neutrophils, and a lower fraction of follicular T helper cells and resting DCs [41,42]. As a result of this intense traffic, any modification in the TME can hypothetically affect the efficacy of ICIs.…”
Section: Role Of Tumour Microenvironment and Myeloid Cellsmentioning
confidence: 99%
“…Through the analysis of immune cell infiltration, it was found that compared with the high expression of WTAP, the low expression group of wtap was significantly higher in neutrophils and eosinophils.It can be concluded that m6A subtype is related to neutrophil extracellular trap (NET) and eosinophil extracellular trap (EET) caused by neutrophils and eosinophils.The clusterB subtype is related to monocyte extracellular trap (MOET) caused by monocytes.EET is composed of DNA fiber network released after activation of eosinophils and granular proteases such as eosinophil cationic protein (ECP) and major basic protein (EOM).Studies have found that activated eosinophils in severe asthma can activate type 2 innate immune lymphocytes through EET to induce steroid resistance [42].Net is a reticular extracellular structure composed of extracellular DNA released by activated neutrophils and neutrophil elastase (NE), myeloperoxidase (MPO) and other degradation enzymes. Studies have shown that enhanced net in COPD patients can be related to airflow restriction and lung tissue injury in COPD patients by activating airway neutrophil inflammation [43].In addition, the study found that MOET can be activated by reactive oxygen species (ROS), showing a similar morphology to net releasing myeloperoxidase (MPO), lactoferrin (LF), elastase and so on, but the release of MOET does not depend on MPO activity [44].Other studies have found that hypoxia can cooperate with inflammatory mediators to promote the release of tissue toxic proteins such as neutrophil elastase (NE), myeloperoxidase (MPO), vascular injury or activated intercellular adhesion molecule (ICAM-1) in COPD to induce endothelial injury [45].Other studies have shown that C5AR1 positive neutrophils can also release inflammatory factors such as IL1 β、 TNF α、ENO1 to promote the growth of breast cancer in patients with breast cancer but m6A methylated WTAP can eliminate this process [46].In addition, leukocyte family chemokine (CXCR1) in COPD patients can bind with ligand IL-8 to activate neutrophil chemotaxis, phospholipase D activation and respiratory burst to induce airflow restriction in COPD patients and promote inflammatory response [47].The global initiative for chronic obstructive pulmonary disease (gold) pointed out that the increased eosinophils in the blood and sputum of COPD patients can not only predict the risk of disease exacerbation, but also predict the effect of glucocorticoid treatment [48].In addition, studies have shown that the increase of blood eosinophils in COPD patients is positively correlated with FeNO value and eosinophils have better lung function performance [49].…”
Section: Discussmentioning
confidence: 99%